Examining Volatility of Interbank Rate in Nepal - Neupane, Suman (NRB Economic Review, 2011)
This paper attempts to examine volatility pattern of interbank rate of Nepal using daily and monthly data. The empirical results show significant variation in volatility during the period of study. It depicts the clustering of large and small variances of interbank rate. Moreover, as the sum of ARCH and GARCH coefficients are greater than unity in the daily interbank rate, shocks are highly persistent in the interbank market. However, the SLF of NRB has been observed to lower the persistence of shocks, as the sum of ARCH and GARCH coefficients decreases when effect of SLF and repo are introduced in the model. It depicts that SLF and repo of NRB has been effective to lower the persistence of shocks on daily interbank market, but it increased the mean of conditional volatility. The other important finding of the study is that mean conditional volatility is highest in February and lowest in August.